INTEGRATED INTERACTION BETWEEN THE JUDICIARY AND THE PUBLIC: THE SEARCH FOR A BALANCED MODEL OF JURY COURT FUNCTIONING - ILIUK, DMYTRO (Ehrlich’s Journal, 2024)
Abstract. The article examines the integrative interaction of the judiciary and the public in the administration of justice through the institution of juries. The prerequisites and reasons for which countries resort to the introduction of a jury trial, refuse it, or change the procedures for considering cases by such courts are outlined. Attention is focused on the disadvantages and advantages of the operation of the jury trial. The legal toolkit, which can be used by the judiciary and the public during integration interaction, is defined. It was established that the possibility of public participation in the administration of justice, firstly, legitimizes the judicial power as one of the branches of state power, secondly, it is an integral attribute of the management system, which professes democratic ideas and principles, thirdly, it becomes a driving force for democratic states to look for effective mechanisms of integration interaction between the judiciary and the public. The necessity of finding an idea around which it is possible to unite supporters and opponents of the functioning of the jury trial is argued. It consists in ensuring a balance between the independence of the jury and the judiciary, as well as the observance of the defendants’ rights. Based on the analysis, a balanced model of interaction between the judiciary and the public through a jury trial is proposed, which consists in the need to: 1) expand the composition of the jury, at least to 9 jurors and three judges, who will decide on the defendant’s guilt by a qualified majority of their members (at least 6 jurors and 2 judges); 2) jurors to refer to the evidence that convinced them of the person’s guilt; 3) the use of "decision trees" in courts, as well as the involvement of the secretary of the court session as a consultant to the jury on legal issues during the discussion of the case.